The Causal Modeling of the Relationship among the Psychological Well Being, Psychological Resilience, and Perceived Social Support - Al-Dababi, Khaldoun Ibrahim; Abdel Rahman, Abdulsalam Hani (Dirasat: Human and Social Sciences, 2024)
Objectives: The objective of this study was to unveil the causal modeling of the relationship among Psychological Well-Being, Psychological Resilience, and Perceived Social Support. Based on scientific foundations, the study constructed a proposed causal relationship model using path analysis to interpret Psychological Well-Being. Methods: To achieve this goal, the study employed the Psychological Well-Being scale by Ryff & Keyes (1995), the Psychological Resilience Scale by Smith, Dalen, Wiggins, Tooley, Christopher & Bernard (2008), and the Perceived Social Support Scale by Zimet, Dahlem, Zimet & Farley (1988). The sample consisted of 310 students who were chosen based on availability. Results: The study results showed no statistically significant differences between the proposed and optimal causal relationship models, with high matches on IFI = 0.99, CFI = 0.99, RMSEA = 0.07, and χ2 = 2.53. Thus, the model constructed the proposed relationships and represented the optimal causal relationship model for the study variables. Conclusions: The model explains the direct and indirect optimal relationships for both self-esteem and the implicit theories of personality and aggressive behavior, providing a deep theoretical grounding. Therefore, these results suggest recommendations for conducting more causal studies to provide a more integrated and comprehensive understanding of personality and its links to various aspects, such as psychological adaptation and personality traits.